Major virus and virus-like diseases of citrus in the Mediterranean - D'Onghia A.M.; Lacirignola C. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
A description of major graft transmissible diseases of citrus is given with particular reference to those which are spread in the Mediterranean countries (tristeza, psorosis complex, infectious variegation, satsuma dwarf, concave gum, cristacortis, impietratura, exocortis, cachexia-xyloporosis, stubborn) and those which may represent a serious threat for this area (tatterleaf, greening).
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)